Protective mechanism of safflower yellow injection on myocardial ischemia-reperfusion injury in rats by activating NLRP3 inflammasome - Lingmei Li; Ce Cao; Hao Guo; Li Lin; Lei Li; Yehao Zhang; Gaojie Xin; Zixin Liu; Shujuan Xu; Xiao Han; Qiong Zhang; Jianhua Fu (BMC Complementary Medicine and Therapies)
Abstract Objectives This study intended to explore whether the protective effect safflower yellow injection (SYI) on myocardial ischemia-reperfusion (I/R) injury in rats mediated of the NLRP3 inflammasome signaling. Methods The I/R model was prepared by ligating the left anterior descending coronary artery for 45 min and then releasing the blood flow for 150 min. 96 male Wistar rats were randomly divided into sham group, I/R group, Hebeishuang group (HBS), SYI high-dose group (I/R + SYI-H), SYI medium-dose group (I/R + SYI-M) and SYI low-dose group (I/R + SYI-L). Cell experiments were divided into normal control group (NC), Oxygen glucose deprivation/reoxygenation group (OGD/R), OGD/R + SYI group, OGD/R + SYI + Chloroquine group (OGD/R + SYI + CQ). The area of myocardial ischemia infarction and pathological changes were observed by the Tetrazolium method (TTC) and HE staining. Myocardial enzymes such as aspartate aminotransferase (AST), lactate dehydrogenase (LDH) and creatine kinase (CK) were measured by chemiluminescence (CL) method. The inflammatory factors levels of TNF-α, IL-1β, MCP-1, and IL-6 were detected by ELISA. The expressions of inflammatory-related proteins (Caspase-1, NLRP3, TLR4, NF-κB), autophagosome-related proteins (LC3-I, LC3-II,LC3-II/LC3-I), apoptosis-related proteins (Bax, Bcl-2, Caspase-3, Bcl-2/Bax) and autophagy-related proteins (p62/SQSTM1, PI3K, p-Akt, mTOR) were detected by Western-Blot. Cell morphology and cell viability were detected by transmission electron microscopy and CCK-8. Results In vivo, compared with sham group, the percentage of myocardial infarction area was increased and myocardial tissue arrangement was disordered in I/R group. In addition, the activities of myocardial enzymes, the contents of inflammatory factors, the expressions of inflammatory-related proteins, autophagy-related proteins, autophagosome-related proteins, Bax and Caspase-3 were increased, while Bcl-2 and Bcl-2/Bax were decreased. SYI treatment reversed these trends, except for the expression of autophagosome-related proteins. In vitro, SYI decreased the contents of inflammatory factors and the expressions of inflammatory-related proteins, autophagy-related proteins and autophagosome-related proteins caused by OGD/R. However, the contents of inflammatory factors and the expression of inflammatory-related proteins, p62/SQSTM1 and mTOR were increased, while PI3K, p-AKT, LC3-II/LC3-I were significantly decreased in OGD/R + SYI + CQ group. Conclusions SYI can promote myocardial tissue autophagy by regulating NLRP3, thereby attenuating the myocardial inflammatory response and protecting damaged myocardium in I/R rats.